The Development of Food Security Model Based on Subak System in Bali - Wayan Windia; Ketut Suamba; Wayan Sudarta (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2010)
-